Discursos e a construção do 'real': um estudo do processo de formação e institucionalização do campo da biotecnologia - Peci, Alketa (2005)
Comprehension of the processes of formation of new organizational fields is the main objective that stimulated the theoretical reflection and empirical research that I present in this paper. My intention here is to uphold the potential for the application of seemingly dichotomous perspectives in terms of the objectivity/subjectivity dimension in the comprehension of the objective in question. The contribution of Foucault, with his concept of discourse, is linked to the proposal of critical constructivism represented by Latour and studies of science and technology. Juxtaposing these perspectives, I examined the dynamics of the biotechnological field on the basis of the dialectic of movements of demarcation/circularity, which is basically a simultaneous movement of (dis)construction of the boundaries of a field. The dialectic of demarcation/circularity is made up of the set of relations established between heterogeneous elements ¿ institutions, economic and social processes, behavioral patterns, systems of norms, techniques, types of classification, forms of characterization, in other words it finds ways of emerging in the course of discursive formations. This theoretical proposal ¿ which incorporates an overlooked dimension in institutional analysis, especially in organization studies (power) ¿ has the advantage of contributing to enhancing comprehension of the dynamics of institutionalization. By proposing that the institutional processes arise within discursive fields, the argument put forward is that such processes contribute to the productivity of the power relations in these fields. In empirical terms, I conducted a descriptive and exploratory research directed at the biotechnology sector. The research was based on a historical perspective, since the analysis spans the period from the origins of genetic science (beginning of the 20th century) through to recent developments in biotechnology in the USA (beginning of the 21st century). The USA was chosen as the locus of research, principally due to the fact that structuring of the field of biotechnology originated in that country, subsequently spreading to other countries around the world. Starting from this theoretical and methodological framework, three discursive formations are highlighted: organization, information and network. Each of the discursive formations is characterized by a dominant set of discourses that prepare the ground for the appearance and (trans)formation of the focus-objects under analysis. In this process, organizations appear in at least two ways: as boundary-organizations ¿ which are important for understanding the movement of the approximation of different discursive domains ¿ and as new organizations, which accompany the (trans)formation of new fields, whereby prevailing discourses materialize at a given historical moment and contribute to breathe life into new discourses, which in turn spark off new power relations. Among the conclusions of this work, I would highlight the following: questioning the 'organizational' dimension of the fields; the relationship revealed not only between the discourses and the institutionalized practices, but also with the process of construction of legitimacy; and the redefinition of the concept of organizations, based on new conceptions relating to the limits of the topic, the objectivity/subjectivity, and space/time dichotomy.